2021
DOI: 10.1109/access.2021.3096988
|View full text |Cite
|
Sign up to set email alerts
|

Introspection Into Reliability Aspects in AlGaN/GaN HEMTs With Gate Geometry Modification

Abstract: Reliability enhancement of AlGaN / GaN HEMT is a significant thrust area due to rapidly improving material and processing technology. In this paper, a detailed analysis of gate-shaped AlGaN / GaN HEMT with field plate is presented. Although AlGaN / GaN HEMT with field-plate is well known, its blending with gate-shaping leading to a more robust and reliable behaviour is described in this paper. It is observed that the threshold voltage and transconductance invariably remain constant for various combinations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…The higher dielectric constant leads to higher gate capacitance (CG) [22] . The dependency between CG and VGS is studied by performing AC analysis with frequency of operation fixed at 1 MHz [23] , source and drain terminals being grounded, and VGS being swept from -6 V to 0 V. In sample C, the HfO2 with a length of 500 nm on the gate side near the drain mostly increases CGD. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The higher dielectric constant leads to higher gate capacitance (CG) [22] . The dependency between CG and VGS is studied by performing AC analysis with frequency of operation fixed at 1 MHz [23] , source and drain terminals being grounded, and VGS being swept from -6 V to 0 V. In sample C, the HfO2 with a length of 500 nm on the gate side near the drain mostly increases CGD. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This adversely affects the device's performance, lifetime, and reliability, limiting the operational capability. Prior work has demonstrated the use of high-k dielectric passivation layer [8,9], field plates (FP) [10,11,12,13,14], and modified gate geometry [15,16,17] to moderate the electric field at the drain side of the gate edge of the device thereby enhancing the breakdown voltage. Zhang et al [18] demonstrated a recessed float field plate in millimeter-wave AlGaN/GaN HEMTs that modulates the electric field distribution at the drain end of the gate edge, thereby increasing the breakdown voltage.…”
Section: Introductionmentioning
confidence: 99%